2008
DOI: 10.1103/physrevlett.101.057005
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Superconducting Transition Temperature ofLa2xSrxCuO4Bilayers: Role of Pairing and Phase Stiffness

Abstract: The superconducting transition temperature T(c) of bilayers comprising underdoped La(2-x)Sr(x)CuO(4) films capped by a thin heavily overdoped metallic La(1.65)Sr(0.35)CuO(4) layer, is found to increase with respect to T(c) of the bare underdoped films. The highest T(c) is achieved for x=0.12, close to the "anomalous" 1/8 doping level, and exceeds that of the optimally doped bare film. Our data suggest that the enhanced superconductivity is confined to the interface between the layers. We attribute the effect t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
85
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 24 publications
6
85
2
Order By: Relevance
“…Another recent discovery of interface superconductivity in complex oxides (1)(2)(3)(4)(5) has also generated some excitement and triggered a debate about its origin and the possibility to enhance T c further (6)(7)(8)(9). The interfacial enhancement (3) of T c is influenced by the crystal structure.…”
mentioning
confidence: 99%
“…Another recent discovery of interface superconductivity in complex oxides (1)(2)(3)(4)(5) has also generated some excitement and triggered a debate about its origin and the possibility to enhance T c further (6)(7)(8)(9). The interfacial enhancement (3) of T c is influenced by the crystal structure.…”
mentioning
confidence: 99%
“…These materials are on either side of the high temperature superconducting "dome" of the T c vs. doping curve, but via charge transfer, superconductivity is found just at the interface. 15,16 It has been suggested that such a separation of a region of strong pairing potential, and a region of high superfluid density, may be an avenue to enhancing T c at interfaces. 17,18 …”
Section: Charge Transfermentioning
confidence: 99%
“…4,[16][17][18][19][20][21][22][23][24][25][26] Nevertheless, these authors propose very different origins for such anomalous precursor diamagnetism, including the presence of superconducting phase fluctuations up to the pseudogap temperature or the existence in the bulk of intrinsic inhomogeneities with short characteristic lengths, as those observed by using surface probes.…”
mentioning
confidence: 99%